UKWMS’ COMMUNITY ENGAGEMENT FOR DEVELOPMENT: PROMOTING ECONOMIC GROWTH THROUGH PRODUCT DEVELOPMENT AND DIGITAL MARKETING AT PUHSARANG KEDIRI - Yuniarto, Antonius; Mawasti, Alpi; Memarista, Gesti; Agung, Deatri Arumsari; Setyawan, Annisa Alfa; Kristanto, Visi Saujaningati; Jonathan, Nicholas (Fakultas Bisnis, Universitas Katolik Widya Mandala Surabaya, 2023)
In the era of globalization, the level of competition for Small and Medium Enterprises is getting tighter, exacerbated by the severe situation of the Covid-19 pandemic, making it difficult for MSMEs to market the products they produce. CED UKWMS 2023 is a form of community activity held in Puhsarang Kediri aimed at increasing the capabilities of MSME partners to grow and develop. The CED will be conducted on July 20-28, 2023, involving 27 participants from 3 countries: the Philippines, Malaysia, and Indonesia. The series of activities carried out at CED in the form of service learning projects focus on product development activities and online markets. The output produced from is in the form of packaging prototype designs, logo designs, stickers, banners. In addition, the output of digital marketing development is in the form of creating social media accounts such as Instagram as a marketing medium for MSME products. In general, CED this time has provided solutions to the problems of MSME partners related to product development and online/digital markets.